The Critical Role of Meaningfulness and Natural Soundscape to Revisit Intention at Tourist Geopark Ciletuh: Eudaimonic Satisfaction and Destination Engagement as a Mediators - Putri Darmayanti Ramadhani; Yadi Ernawadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of novelty, meaningfulness, natural landscape, and natural soundscape on the revisit intention of Ciletuh Geopark tourists through eudaimonic satisfaction and destination engagement using the stimulus-organism-response (S-O-R) framework. The study used a survey method with a quantitative approach involving 160 tourist respondents who had visited the Ciletuh Geopark. Data was collected through questionnaires and analyzed using PLS-SEM with SmartPLS 3.0. Of the eighteen hypotheses proposed, nine hypotheses were supported by empirical data. The results showed that eudaimonic satisfaction mediated the influence of meanigfulness on revisit intention, while destination engagament mediated the influence of meaningfulness and natural soundscae on revisit intention. The results of this research are expected to be an input for the manager of the Ciletuh Geopark to prioritize increasing meaninfulness, followed by natural soundscape, in order to increase revisit intention through eudaimonic satisfaction and destination engagement. The findings of this study provide a basis for the development of a conceptual model through testing other variables that are relevant in increasing tourist revisit intention.